2016
DOI: 10.1038/srep21576
|View full text |Cite
|
Sign up to set email alerts
|

Visualising the molecular alteration of the calcite (104) – water interface by sodium nitrate

Abstract: The reactivity of calcite, one of the most abundant minerals in the earth’s crust, is determined by the molecular details of its interface with the contacting solution. Recently, it has been found that trace concentrations of NaNO3 severely affect calcite’s (104) surface and its reactivity. Here we combine molecular dynamics (MD) simulations, X-ray reflectivity (XR) and in situ atomic force microscopy (AFM) to probe the calcite (104) – water interface in the presence of NaNO3. Simulations reveal density profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…Thanks to recent advances in AFM technology, it is now possible to obtain images or movies containing isolated imperfections in a periodic structure [16,17]. However, these experimental studies have not been able to interpret what they have observed, due to the lack of knowledge regarding the imaging mechanism.…”
mentioning
confidence: 99%
“…Thanks to recent advances in AFM technology, it is now possible to obtain images or movies containing isolated imperfections in a periodic structure [16,17]. However, these experimental studies have not been able to interpret what they have observed, due to the lack of knowledge regarding the imaging mechanism.…”
mentioning
confidence: 99%
“…For example, Voitchovsky and Schmidt et al investigated calcite (104)-water interface in the presence of NaNO 3 [175]. In situ AFM images confirmed the alteration of crystallographic characteristics, and AFM force spectroscopy indicated the ability of dissolved NaNO 3 to modify the structure of interfacial water.…”
Section: Calcitementioning
confidence: 97%
“…High-resolution amplitude modulation atomic force microscopy (AFM) in liquid 23 is used to explore in situ the sub-nanometre details of the resulting interfacial molecular assemblies. When operated in solution and at small amplitude, the technique can routinely provide molecular-level details of the interface, 24,25 including of solvation structures 26,27 and stable supramolecular assemblies. 21 The AFM results include simultaneously acquired topographic and phase images of the interface.…”
Section: Adjunction Of Small 'Influencer' Moleculesmentioning
confidence: 99%